Problem solving and critical thinking for designers - Piotrowski, Christine M., 1947- (Hoboken, N.J. : Wiley, 2011)
"Bestselling author Christine M. Piotrowski users her trademark accessible and conversational approach to explain how the working designer solves problems and makes decisions by having the reader follow through case studies and stories, and dealing with a variety of situations. A special section presents a selection of scenarios or documents with problems, and permits the reader to work through for a solution. Whether dealing with a design problem or with a client, Critical Thinking for Designers will put the reader on the correct path to a solutions-oriented practice"--
"Piotrowski explains how the working designer solves problems and makes decisions by having the reader follow through case studies and stories, dealing with a variety of situations"--
Includes bibliographical references (p. 167-174) and index.
Keywords: Architectural design -- Decision making -- Problems, exercises, etc; Interior architecture -- Decision making -- Problems, exercises, etc; ARCHITECTURE / Interior Design / General